CP-226 Safety of direct acting antiviral and antiretrovirals drugs in HCV patients co-infected with HIV-1: Clinical practice experience. (14th February 2016) - Cañamares-Orbis, I; Izquierdo-Garcia, E; Escobar, I; Esteban-Alba, C; Saez, J; Such-Diaz, A; Barrueco-Fernandez, N; Ryan, P; Troya, J
Abstract : Background: For novel direct acting antiviral (DAA) drugs, HIV/hepatitis C virus (HCV) patients have achieved similar sustained virologic response rates as HCV monoinfected patients, but experience in safety and drug interactions with antiretroviral (ARV) regimens are limited in clinical practice, especially in cirrhotic patients. Purpose: We evaluated the safety of DAA and ARV drugs in HCV patients co-infected with HIV-1, treated at the hospital from January to September 2015. Material and methods: HCV/HIV patients on stable ARV regimens were enrolled and received HCV-AAD treatments sofosbuvir/ledipasvir (SOF/LDV), ombitasvir/paritaprevir/ritonavir plus dasabuvir (OTV/PTV/r+DSV) and sofosbuvir plus daclatasvir, simeprevir or ribavirine for at least 4 weeks. Patients with compensated cirrhosis were eligible. All requests for HCV treatment initiation were validated by a pharmacist with a checklist designed for it, taking into account drug interactions and adequacy recommendations. Safety evaluation was the primary endpoint and included frequency and severity of adverse events (AEs) and standard laboratory parameter monitoring in addition to enhanced renal toxicity monitoring. CD4 count and HIV-1 RNA levels were measured to detect HIV virologic rebound. Results: 22 patients were enrolled, 86% had cirrhosis and 86% had no prior HCV treatment. 76% were treated with SOF/LDV, 9% with OTV/PTV/R+DSV and 18% with other treatments. 41% had genotype (GT)1a, 23% GT1b, 4% GT2, 14% GT3 and 23% GT4. 86% were male, 96% were white and mean age was 51 (range 41–59) years. Mean baseline HCV RNA was 6.28 log10 IU/mL (range 5.9–7.0) and mean baseline CD4 count was 326 cells/uL (IQR=267). 68% completed 12–24 weeks of treatment and 32% are currently on treatment. 96% patients achieved undetectable HVC viral load at week 4. Patients were taking NRTIs (TDF/FTC 41%; ABC/3TC 45%) or nucleotide free regimens 14%), integrase inhibitor (RAL or DTG) (58%), IPs (DRV or ATV)(29%) or NNRTIs (RPV, ETV, NVP) (13%). One patient had confirmed HIV virologic rebound (HIV-1-RNA ≥400 copies/mL), possibly related to DTG drug intolerance. No patients discontinued HCV treatment due to an AE. AEs occurring in ≥10% of patients were headache (32%), fatigue (25%) and nauseas (13%). No significant laboratory abnormalities were observed. Conclusion: In our study, concomitant administration of oral HCV DAA and habitual ARV drugs were safe and well tolerated, including those patients with cirrhosis. This study will continue because more patients are needed to confirm these results. No conflict of interest.